25x-12=7x

Simple and best practice solution for 25x-12=7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25x-12=7x equation:


Simplifying
25x + -12 = 7x

Reorder the terms:
-12 + 25x = 7x

Solving
-12 + 25x = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-12 + 25x + -7x = 7x + -7x

Combine like terms: 25x + -7x = 18x
-12 + 18x = 7x + -7x

Combine like terms: 7x + -7x = 0
-12 + 18x = 0

Add '12' to each side of the equation.
-12 + 12 + 18x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 18x = 0 + 12
18x = 0 + 12

Combine like terms: 0 + 12 = 12
18x = 12

Divide each side by '18'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| x+y=7x-y=5 | | (7-z)(5z+4)=0 | | x+13.9=-7.5 | | X(40+x)=6000 | | -33+53= | | 8x+5z=5+5y | | 7=x(-13+x)-11+6x | | 4x^2-16x=-y^2+10y-40 | | 9x+4x+3+8=4x+3x+8x | | lnx=-1/5 | | 5y-4=13y+68 | | 4x+22=3+7x-8 | | 1/3(x-4)^=1 | | (2000(1-x/60)^2)/x | | 6+1-2x=5x+x-7 | | (5x+20)(3x+66)= | | 6x+7z=4+5y | | Ydy/dx-e^x=O | | 7(2x-9)=43 | | (2s-3)+s+(3s-30)=207 | | r+21=15 | | 5x-3=12+x-1+2 | | 40+2*5= | | k^4-100k=0 | | 3/2x-1/3x | | 0=-16t^2+4.5t | | 16c^2-70c+49=0 | | 1/2=d/4 | | 8-x=3x+8 | | 3x+1x=36 | | y/50=-21 | | 2x^4-13x^2+17=0 |

Equations solver categories